Cop watch spectators, social media, and police reform - Toch, Hans (Psychology, crime, and justice series, 2012)
"This book discusses alterations in the role of the new media in amplification of (primarily) negative views of policing. It also shows changes in the sources that shaped public opinion in the last 30 years. It later highlights changes in policing and the views of the police and their craft in this same period. Alterations in the police occupational culture and public political activities of police spokespersons were described as well as changes in the role of police and policing in the 'high politics' of the city. Lastly changes in police leadership and presentational rhetoric in recent years were pointed out"--Preface. (PsycINFO Database Record (c) 2012 APA, all rights reserved)